CREATING SUPPLY CHAIN EXCELLENCE DURING CORONA PANDEMIC: Swisstec Sourcing Vietnam Ltd. - Dang, An (2020)
Throughout history, the supply chain has always faced inevitable risks, for example, Japanese’s earthquake and tsunami, volcano eruption in Iceland, Thailand’s floods, hurricanes in the United States. However, the impact of these disasters on the supply chain is incomparable to the Corona pandemic, with the lock-down situations in many Asian countries, they have created global supply chain disruption. Many companies found themselves unprepared for the pandemic. External risks are inevitable, however, with excellent internal management, these risks can be minimized. Many re-searches were conducted and many concepts related to supply chain management were introduced to help companies give a better performance of their whole supply chain. The aim of this thesis is to detect the infection of Covid-19 pandemic on the global supply chain network, to understand the supply chain excellence concept and to apply it into businesses in order to adapt to the pandemic disruption and be prepared for a similar situation in future. The final goal is to analyze the difficulties which the case company faced during the pandemic and give suggestions of how to move its supply network to an excellent supply chain during the Corona pandemic. The thesis is written using a deductive reasoning approach, using only qualitative methods of research. Qualitative methods are used to interpret interview responses. Primary data was collected from the interviews of three representatives. The secondary information is collected from various reliable sources, for example, books, articles, and internet sources in order to support the primary data. The study results of the analysis show that Swisstec Sourcing is managing their supply chain in a excellent way, with all commiments under the 4R’s concept. However, they needs to improve their supply chain risk management and be more proactive in handling the risks.